An Evolutionary Conserved Signaling Network Between Mouse and Human Underlies the Differential Osteoskeletal Potential of Frontal and Parietal Calvarial Bones - Menon, Siddharth; Huber, Julika; Duldulao, Chris; Longaker, Michael T.; Quarto, Natalina (Frontiers in Physiology, 2021)
The mammalian calvarial vault is an ancient and highly conserved structure among species, however the mechanisms governing osteogenesis of the calvarial vault and how they might be conserved across mammalian species remain unclear. The aim of this study was to determine if regional differences in osteogenic potential of the calvarial vault, first described in mice, extend to human. We derived human frontal and parietal osteoblasts from fetal calvarial tissue, demonstrating enhanced osteogenic potential both in vitro and in vivo of human frontal derived osteoblasts compared to parietal derived osteoblasts. Furthermore, we found shared differential signaling patterns in the canonical WNT, TGF-β, BMP and FGF pathways previously described in the mouse to govern these regional differences in osteogenic potential. Taken together, our findings unveil evolutionary conserved similarities both at functional and molecular level between the mouse and human calvarial bones, providing further support that studies employing mouse models, are suitable for translational studies to human.